2018
DOI: 10.1007/s10661-017-6459-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights on bioremediation of polycyclic aromatic hydrocarbons using microalgae: a modelling-based computational study

Abstract: Research on bioremediation of polycyclic aromatic hydrocarbons (PAHs) has established that several remediating microbial species are capable of degrading only low molecular weight (LMW)-PAHs, whereas high molecular weight (HMW)-PAHs are hardly degradable. In the present study, the efficiency of degradation of both LMW and HMW-PAHs by cytochrome P450 monooxygenase (CYP) of microalgae was studied. CYP have a key role in the detoxification of xenobiotics. So far, the structure of CYP in microalgae is not predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Specifically, 18 PAHs interacted with Threonine282 (Thr282), Alanine337 (Ala337), Serine404 (Ser404), and Lisyne407 (Lys407) via hydrogen bonds. However, in this study, it is evident that only LMW-PAHs were able to bind CYP450, whereas HMW-PAHs were not [25]. Based on this, this preliminary study aimed to study the potential of H. pluvialis for crude oil bioremediation, analyzing (i) the ability to grow in the presence of such a toxic agent; (ii) the quantitative concentration of hydrocarbons degraded in the aqueous phase and biomass, and (iii) the ability of H. pluvialis to grow in heterotrophic conditions.…”
Section: Introductioncontrasting
confidence: 48%
“…Specifically, 18 PAHs interacted with Threonine282 (Thr282), Alanine337 (Ala337), Serine404 (Ser404), and Lisyne407 (Lys407) via hydrogen bonds. However, in this study, it is evident that only LMW-PAHs were able to bind CYP450, whereas HMW-PAHs were not [25]. Based on this, this preliminary study aimed to study the potential of H. pluvialis for crude oil bioremediation, analyzing (i) the ability to grow in the presence of such a toxic agent; (ii) the quantitative concentration of hydrocarbons degraded in the aqueous phase and biomass, and (iii) the ability of H. pluvialis to grow in heterotrophic conditions.…”
Section: Introductioncontrasting
confidence: 48%
“…Specifically, 18 PAHs interacted with Threonine282 (Thr282), Alanine337 (Ala337), Serine404 (Ser404) and Lisyne407 (Lys407) via hydrogen bonds. However, in this study, it is evident that only LMW-PAHs were able to bind CYP450, while HMW-PAHs did not [48]. Therefore, there is an antioxidant mechanism for the degradation of petroleum pollutions, in particular, hydrocarbons.…”
Section: Mechanism Of Actionmentioning
confidence: 54%
“…SureshKumar et al, suggested a similarity between microalgae and prokaryotes in PAH degradation mechanisms, focusing on the CYP450 oxidative system. Low-molecular-weight PAHs can interact with CYP450, potentially forming hydrogen bonds [168]. An antioxidant mechanism for petroleum degradation emerges, removing toxins and generating growth-supporting nutrients.…”
Section: Microalgae Role In Petroleum Remediationmentioning
confidence: 99%